Pelanggaran Persaingan Usaha dan Problematika Eksekusi Atas Putusan KPPU - Arifin Ma’ruf (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
The genesis of Law No. 5 of 1999 on Prohibition Monopili and UnfairBusiness Competition is expected to be a solution to the problem of unfair businesscompetition that had been rife in Indonesia, the Commission dirikanya spirit in orderto "mensehatkan" business competition in Indonesia. Healthy competition would have apositive impact on entrepreneurs who compete against each other or compete as it maylead to efforts to increase efficiency, productivity, and quality of product produced. Theresults of this study show that the breach of competition rife in Indonesia is bid rigging,In addition there are the problems in the execution of the KPPU decision. This paperwill discuss the tender conspiracy that inhibit competition and problematic execution ofthe Commission's decision.